Fatores associados à não adesão do portador de diabetes mellitus tipo 2 aos antidiabéticos orais - Freitas, Roberto Wagne Júnior Freire de (2010)
Non-compliance to drug therapy in patients with Diabetes Mellitus type 2 (DM 2) has been observed by health professionals as a major problem for the mantaining the glucose balance. In addition, there are many factors that can influence the non-compliance of patients with DM 2 to oral drugs, and there is no consensus about which ones have the most influence. This study aims to determine the factors that affect the non-compliance to drug therapy with oral antidiabetics in patients with DM 2. This is a non-experimental study, with descriptive and cross-sectional aproach, performed with 377 patients non-adherents to drug treatment, both sexes, aged between 18 and 92 years. The research was conducted during the months from March to July 2009, in 12 Family Health Centers (CSF) of Fortaleza – CE. Two units of each of the six regions have being chosen, for convenience. A formulary was used for the collection of sociodemographic, clinical and therapy information. The data were triple typing and stored in the software SPSS. In order to verify the existence of associations between dependent and causal variables, we made crossed tables and we applied the Qui-square test and Fisher test. A significance level of 5% was set for all tests. As a result, it was found that 69.5% of the sample were female, 30.5% were located in the age group of 60-69 years, 47.7% were white, 57.0% had a consensual union or were married, 48.0% were retired, 48.3% were part of the socioeconomic class D, 37.7% had, as schooling, the incomplete primary and 69.0% were catholics. By making associations between non-compliance and sociodemographic variables, prevailed male subjects (88.5%), those of younger age (89.8%), those with yellow skin (90.9%), those who had high school (94.1%), couples (87.4%) and those with a better socioeconomic status (92.9%). It wasn´t found statistical significant associations in none of these crossings (p = 0.386, p = 0.181, p = 0.635, p = 0.786, p = 0.846 and p = 0.626, respectively). Individuals who have some employment (formal and informal) or who were self-employed, were the patients who had higher non-compliance to oral hypoglycemic agents (p = 0.048). Regarding the clinical factors, non-compliance was statistically associated with absence in consultations (p = 0.000), use of other drugs in addition to oral hypoglycemic agents (p = 0.039), use of alcohol (p = 0.005) and changes in blood glucose levels (p = 0.013). It wasn´t found statistical association between non-compliance and the receiving of recommendations about how to take the medications (p = 0.325), as well as the understanding of the given information (p = 0.426) and the receipt of any explanatory material about DM 2 (p = 0.081). Other studies should be developed so that new populations can be investigated, new factors can be indentified and new associations can be found. Moreover, investigations with the aim of evaluate interventions, as health education strategies, can be planned.